The analytics of the New Keynesian 3-equation Model - Poutineau, Jean-Christophe; Sobczak, Karolina; Vermandel, Gauthier (Economics and Business Review, 2015)
This paper aims at providing a self contained presentation of the ideas and solution procedure of New Keynesian Macroeconomics models. Using the benchmark “3 equation model”, we introduce the reader to an intuitive, static version of the model before incorporating more technical aspects associated with the dynamic nature of the model. We then discuss the relative contribution of supply, demand and policy shocks to the fluctuations of activity, inflation and interest rate, depending on the key underlying parameters of the economy.